STRATEGI PEMBELAJARAN GURU DALAM MEMBENTUK KECERDASAN SPIRITUAL PESERTA DIDIK DI MADRASAH IBTIDAIYAH MUHAMMADIYAH KABUPATEN FAKFAK PAPUA BARAT - Salman, Muhammad; Rasyid, Muhammad Rusdi; Huzein, Muhammad (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2024)
The objectives of this scientific research are: 1) To describe teachers' teaching strategies in building students' spiritual intelligence at Madrasah Ibtidaiyah Muhammadiyah, Fakfak Regency, West Papua. 2) To describe the supporting and inhibiting factors in implementing teachers’ teaching strategies in building students' spiritual intelligence at Madrasah Ibtidaiyah Muhammadiyah Fakfak Regency, West Papua. 3) To describe the impact of teachers' teaching strategies in forming students' spiritual intelligence at Madrasah Ibtidaiyah Muhammadiyah, Fakfak Regency, West Papua. This research applied descriptive a qualitative method. Primary data sources are class teachers, Islamic Education teachers, and Tahfiz Qur'an teachers for grades V and VI. Data collection methods are observation, interviews, and documentation. The data were processed and analyzed through reduction, presentation, and conclusion. The results show that: 1) Teacher teaching strategies in building students' spiritual intelligence are: a) Learning methods, b) Memorizing (Tahfiz) al-Qur'an, c) Islamic education methods, d) Extracurricular activities, e) Action social fundraising and joint prayer for Palestine.